The Influence of Leadership Style, Work Effectiveness, and Career Development, on Employee Performance in BNN Bogor Regency with Motivation as an Intervening Variable - Damela Putra; Slamet Ahmadi (Jurnal Syntax Admiration, 2024)
leadership style, work effectiveness, and career development are three of several factors that are thought to be relatively large in influencing employee performance at BNN Bogor Regency with motivation as an intervention variable. The research was conducted at BNN Bogor Regency by taking a sample of 85 respondents who were calculated using the Saturated Sempel formula. Methods of data collection with the questionnaire method where the data processed is primary data obtained by data analysis method with multiple linear regression analysis. To determine employee performance can be measured by the variables of leadership style, work effectiveness, and career development and motivation as interventions. The results of this study indicate that leadership style, work effectiveness, and career development and motivation as intervening influence employee performance. this is evidenced by the value of Sig 0.000 > 0.05, it can be concluded that Ho is rejected Ha is accepted, so the conclusion is partially leadership style, work effectiveness, and career development and motivation as interventions that affect employee performance.